A Multi-State Model Examining Patterns of Transitioning Among States of Engagement in Care in HIV-Positive Individuals Initiating Combination Antiretroviral Therapy. (15th December 2016) - Gillis, Jennifer; Loutfy, Mona; Bayoumi, Ahmed M.; Antoniou, Tony; Burchell, Ann N.; Walmsley, Sharon; Cooper, Curtis; Klein, Marina B.; Machouf, Nima; Montaner, Julio S. G.; Rourke, Sean B.; Tsoukas, Christos; et al.
Abstract : Background: Common measures of engagement in care fail to acknowledge that infrequent follow-up may occur either intentionally among patients with sustained virologic suppression or unintentionally among patients with poor clinical outcomes. Methods: Five states of HIV care were defined within the Canadian Observational Cohort Collaboration following combination antiretroviral therapy (cART) initiation: (1) guidelines HIV care [suppressed viral load (VL) and CD4 >200 cells per cubic millimeter, no gaps in cART >3 months, no gaps in CD4 or VL measurement >6 months], (2) successful care with decreased frequency of follow-up (as above except no gaps in CD4 or VL measurement >12 months), (3) suboptimal care (unsuppressed VL, CD4 <200 cells per cubic millimeter on 2 consecutive visits, ≥1 gap in cART >3 months, or ≥1 gap in CD4 or VL measurement >12 months), (4) loss to follow-up (no contact for 18 months), and (5) death . Multi-state models were used to determine factors associated with transitioning among states. Results: In total, 7810 participants were included. Younger age, female gender, Indigenous ethnicity, and people who have injected drugs were associated with increased likelihoods of transitioning from guidelines to suboptimal care and decreased likelihoods of transitioning from suboptimal to guidelines care. One-fifth of individuals in successful, decreased follow-up after cART initiation (mean sojourn time 0.72 years) were in suboptimal care in subsequent years. Conclusions: Using routinely collected data, we have developed a flexible framework that characterizes patient transitions among states of HIV clinical care. We have demonstrated that multi-state models provide a useful approach to supplement "cascade of care" work. Abstract : Supplemental Digital Content is Available in the Text.